PRIMARY PREVENTION OF CERVICAL CANCER WITH VIDEO MEDIA FOR POSYANDU CADRES - Ni Made Puspita Dewi; Ni Komang Erny Astiti; I Nyoman Wirata; Ni Wayan Suarniti; Lely Cintari; Ni Made Dwi Purnamayanti (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Cervical cancer is one of the malignancies of the female reproductive organs with a long pathophysiology. Early detection with Visual Acetate Inspection (VIA) and Pap Smear can prevent poor prognosis. However, the evaluation of the coverage of the achievement of the program is still low. The study aimed to analyze the effectiveness of primary prevention education on cervical cancer using video media to increase the knowledge of posyandu cadres. Type of experimental research categorical paired. The sample was 56 posyandu cadres who were selected by purposive sampling. Knowledge data collection was done with pretest and posttest questionnaires. Data analysis was performed with Wilcoxon (ρ=0.005). The results showed an increase in the median value of knowledge pretest 65.00 to the posttest median of 85.00. Video media effectively increases the knowledge of posyandu cadres about the early detection of cervical cancer (ρ=0.000). Health education with video media proved effective in increasing the knowledge of posyandu cadres about the primary prevention of cervical cancer. It is hoped that this study can contribute to improving the ability of human resources in promotive efforts through interactive media-based health promotion.